0
$\begingroup$

$$\arctan 2x +\arctan 3x = \left(\frac{\pi}{4}\right)$$ $$\arctan \left(\frac{2x+3x}{1-2x*3x}\right)=\frac {\pi}{4}$$ $$\frac {5x}{1-6x^2}=\tan \frac{\pi}{4}=1$$ $$6x^2 + 5x -1 = 0$$ $$(6x-1)(x+1)=0$$ $$x=-1, \frac{1}{6}$$

The answer however rejects the solution $x=-1$ saying that it makes the L.H.S of the equation negative. I don't understand this, I don't see how $x=-1$ makes the L.H.S. negative.

$\endgroup$
1
$\begingroup$

Because $$\arctan(-2)+\arctan(-3)=-135^{\circ}<0$$ By the way, $\tan(-135^{\circ})=1.$

$\endgroup$
  • $\begingroup$ but then isn't -1 a valid solution? $\endgroup$ – Raknos13 Dec 15 '17 at 8:17
  • 1
    $\begingroup$ @mettled mike You can see that $-1$ is not root of the equation. We see that $\tan45^{\circ}=\tan(-135^{\circ})$, but $\arctan\tan45^{\circ}\neq-135^{\circ}.$ $\endgroup$ – Michael Rozenberg Dec 15 '17 at 8:19
0
$\begingroup$

$\tan(x)$ is negative in the interval $\left(-\frac{\pi}{2},0\right)$, so it's inverse on the interval $(-\infty,0)$ will give a value from the interval $\left(-\frac{\pi}{2},0\right)$.

$\endgroup$
0
$\begingroup$

$\arctan x + \arctan y = \arctan\left(\dfrac{x+y}{1-xy}\right), \quad\quad xy < 1$

So

$x = -1$ doesn't work as $2x \times 3x = 6x^2 = 1 \nless 1$.

$x=\frac16$ works as $6x^2 = \frac1{6} \lt 1$.

$\endgroup$
-1
$\begingroup$

Concep: Let $f$ be a function, which means $$x_1=x_2\Rightarrow f(x_1)=f(x_2)$$ But note that if $f(x_1)=f(x_2)$, then $x_1=x_2$ is one of the possibility, among perhaps many possibilities if the function is not injective

Now Given $\tan^{-1}(2x)+\tan^{-1}(3x)=\frac{\pi}{4}$, taking $\tan$ of both sides(since $\tan$ is a function),we get $$\frac{2x+3x}{1-2x.3x}=1$$

which after simplification gives $x=\frac16,-1$. Taking $x=\frac16$, we want to find what is $\tan^{-1}\frac13+\tan^{-1}\frac12$. For that let us take $\tan^{-1}\frac13=\alpha,\tan^{-1}\frac12=\beta$, which is equal to $\tan\alpha=\frac13,and \tan\beta=\frac12$, where $\alpha,\beta$ being principal values belongs to $(-\frac{\pi}2,\frac{\pi}2)$, which means $\alpha+\beta\in(-\pi,\pi)$. Now we know $$\tan(\alpha+\beta)=\frac{\tan\alpha+\tan\beta}{1-\tan\alpha\tan\beta}$$ which implies $$\tan(\alpha+\beta)=\frac{\frac13+\frac12}{1-\frac13\frac12}=1$$ Hence $$\alpha+\beta=\tan^{-1}1=\frac{\pi}4$$ or $$\tan^{-1}\frac13+tan^{-1}\frac12=\frac{\pi}4$$ and $x=\frac16$ becomes a root of the above equation

Now take $x=-1$, then the lhs of the equation becomes $$\tan^{-1}(-2)+\tan^{-1}(-3)$$ which is a negative angle $-\frac{3\pi}{4}$ , which can not be a positive number $\frac{\pi}{4}$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.